Sr5Os3O13: A mixed valence osmium(v,vi) layered perovskite variant exhibiting temperature dependent charge distribution - Mohitkar, Shrikant A.; Nuss, Juergen; Hoeppe, Henning A.; Felser, Claudia; Jansen, Martin (Dalton Transactions, 2018)
New Sr5Os3O13, as synthesized from binary constituents, exhibits several uncommon features. Its crystal structure is dominated by quasi-2D poly-oxoanions that correspond to unprecedented cutouts of the perovskite type of structure, where corner sharing (OsO6) octahedra aggregate to form terraced slabs. The Os5+/Os6+ mixed valence oxide displays a particular charge ordering scheme. One osmium atom (Os1) per formula unit is in the valence state of 5+ in the whole temperature range studied, while the two remaining sites (Os2A and Os2B) show full charge disorder at high temperatures, resulting in an average charge of 5.5+. The latter, however, apparently undergo a process of continuous charge ordering at cooling. Full charge order appears to be established concomitantly with a phase transition to an antiferromagnetically ordered state at T(Néel) = 170 K. This kind of temperature dependent continuous charge ordering is reflected by structural changes with temperature as well as by changes in paramagnetic response above T(Néel). Disentangling the intimate interplay between magnetic and charge ordering degrees of freedom will require applying sophisticated spectroscopy and (neutron) diffraction techniques.
CRIS-Team Scopus Importer:2022-04-14